The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.2334/josnusd.18-0153
|View full text |Cite
|
Sign up to set email alerts
|

Associations between caries experience, dietary habits, and metabolic syndrome in Japanese adults

Abstract: Dental caries could be a risk factor for metabolic syndrome (MetS); however, there is limited evidence of such a relationship in the literature. This cross-sectional study investigated the relationships among dental caries experience, dietary habits, and MetS in Japanese adults. A total of 937 participants aged 40-74 years underwent a health check, including dental examination. Decayed, missing, and filled teeth (DMFT) were used as an index of caries experience. The mean DMFT score was 14, and 12% of the parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 30 publications
1
17
1
2
Order By: Relevance
“…Additionally, lower socioeconomic status and poor toothbrushing habits were risk factors for dental caries only. Conclusion: Increased BMI in children and adolescents was significantly associated with increased risk for erosive tooth wear (BEWE) and dental caries (DMFT/dmft, ICDAS) Metabolic syndrome Iwasaki et al [ 64 ] Evaluate association between metabolic syndrome, diet and dental caries in Japanese adults by comparing participants with and without metabolic syndrome Cross sectional 937 Japan Outcomes: For diet, significant differences were noted between participants with and without metabolic syndrome for consumption of dairy products ( p < 0.01), bean products, sweets and coffee ( p < 0.05 each); for clinical parameters, significant differences were noted between groups for gender, age, Brinkman index, BMI, waist circumference, blood pressure-both systolic and diastolic, serum fasting blood glucose, high-density lipoproteins (HDL) cholesterol and CRP ( p < 0.001 each); for oral disease, significant difference was noted between periodontitis and DMFT ( p < 0.05 each); multivariate logistic regression analysis after adjusting for confounders showed association between metabolic syndrome prevalence and DMFT (first vs. fourth quartile, OR=1.8 and p>0.05) Conclusion: There appears to be positive association between caries and metabolic syndrome in Japanese adults. This association was strong in those with higher DMFT regardless of dietary habits Adachi et al [ 65 ] Human prospective study of one-year duration to understand relationship between dental caries, periodontitis, and metabolic syndrome (MetS).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, lower socioeconomic status and poor toothbrushing habits were risk factors for dental caries only. Conclusion: Increased BMI in children and adolescents was significantly associated with increased risk for erosive tooth wear (BEWE) and dental caries (DMFT/dmft, ICDAS) Metabolic syndrome Iwasaki et al [ 64 ] Evaluate association between metabolic syndrome, diet and dental caries in Japanese adults by comparing participants with and without metabolic syndrome Cross sectional 937 Japan Outcomes: For diet, significant differences were noted between participants with and without metabolic syndrome for consumption of dairy products ( p < 0.01), bean products, sweets and coffee ( p < 0.05 each); for clinical parameters, significant differences were noted between groups for gender, age, Brinkman index, BMI, waist circumference, blood pressure-both systolic and diastolic, serum fasting blood glucose, high-density lipoproteins (HDL) cholesterol and CRP ( p < 0.001 each); for oral disease, significant difference was noted between periodontitis and DMFT ( p < 0.05 each); multivariate logistic regression analysis after adjusting for confounders showed association between metabolic syndrome prevalence and DMFT (first vs. fourth quartile, OR=1.8 and p>0.05) Conclusion: There appears to be positive association between caries and metabolic syndrome in Japanese adults. This association was strong in those with higher DMFT regardless of dietary habits Adachi et al [ 65 ] Human prospective study of one-year duration to understand relationship between dental caries, periodontitis, and metabolic syndrome (MetS).…”
Section: Resultsmentioning
confidence: 99%
“…Although there are no evidence of relationship DMF and cancer incidence or survival rate of cancer, so on, a positive association between caries experience and metabolic syndrome in Japanese adults were reported recently [29]. In the future, studies which showed the relationship between caries experience or the number of sound teeth and incidence or prognosis of cancer might increase gradually.…”
Section: Enhanced Recovery After Surgery (Eras) Programs Pay Attention To Reducing the Length Ofmentioning
confidence: 95%
“…We have also analyzed the associations between MetS and the diagnosis of "SOS teeth", which are the first priority teeth for treatment due to advanced caries reaching the pulp chamber or the presence of root fragments [12]. In other studies, instead of using pathologies as dental outcomes, the dental-MetS associations were analyzed using dental/periodontal indices as outcomes, including the Decayed, Missing, and Filled teeth (DMFT) index [6,7,13,14], the Community Periodontal Index (CPI) [15,16], clinical attachment loss (CAL) [16,17], plaque index (PI), gingival index (GI), pocket depth (PD) [18], and tooth mobility [19]. Previously, we explored the associations of hypertension diagnosis with dental treatment needs and actual dental treatments [20].…”
Section: Introductionmentioning
confidence: 99%
“…For example, a genome-wide association study (GWAS) for interleukin-1ÎČ levels in gingival crevicular fluid identified IL37 variants that modulate the inflammatory cascade in periodontal disease [29]. It has been reported that several pro-inflammatory cytokines, including IL-1, -6, and -8, upregulate the secretion of MMP-3, which increased with the progression of periodontitis and was involved in the regulation of IL-1ÎČ expression in gingival tissues [14].…”
Section: Introductionmentioning
confidence: 99%